Effects of Ivabradine on Residual Myocardial Ischemia after PCI Evaluated by Stress Echocardiography. (1st April 2019) - Calcagno, Simone; Infusino, Fabio; Dettori, Olga; Taccheri, Temistocle; Bruno, Pasqualina; Maestrini, Viviana; Sardella, Gennaro; Mancone, Massimo; Fedele, Francesco
Abstract : Background . Residual angina after PCI is a frequently occurring disease. Ivabradine improves symptoms but its role in patients without left ventricular systolic dysfunction is still unclear. The aim was to quantify the effects of ivabradine in terms of MVO2 indicators and diastolic function. Methods . Twenty-eight consecutive patients with residual angina after PCI were randomized to ivabradine 5 mg twice/day (IG) or standard therapy (CG). All patients performed a stress echocardiography at the enrollment and after 30 days. MVO2 was estimated from double product (DP) and triple product (TP) integrating DP with ejection time (ET). Diastolic function was evaluated determining E and A waves, E′ measurements, and E/E′ ratio both at rest and at the peak of exercise. Results . The exercise time was longer in IG 9′49″ ± 48″ vs 8′09″ ± 59″ in CG (p = 0.0001 ), reaching a greater workload (IG 139.3 ± 13.4 vs CG 118.7 ± 19.6 Watts;p = 0.003 ). MVO2 expressed with DP and TP was significantly higher in IG (DP: IG 24194 ± 2697 vs CG 20358 ± 4671.8, p = 0.01 ; TP: IG 17239 ± 4710 vs CG 12206 ± 4413, p = 0.007 ). At peak exercise, the ET was diminished in IG than CG. The analysis of diastolic function after the exercise revealed an increase of E and A waves, without difference in the E/A ratio. The E′ wave was higher in IG than CG, and in the same group, the differences between baseline and peak exercise were greater (∆E′3.14 ± 0.7 vs 2.4 ± 1.13, p = 0.047 ). The E/E′ ratio was reduced in patients treated with ivabradine (IG 10.2 ± 2.0 vs CG 7.9 ± 1.6, p = 0.002 ). Conclusions . Ivabradine seems to produce a significant improvement of ischemic threshold, chronotropic reserve, and diastolic function.